MOLECULAR CHARACTERIZATION OF FUSARIUM OXYSPORUM F. SP. CICERI USING SCAR MARKERS - DEBASHRE BHATTACHARJEE; S. S. MANE; JAYASHREE BHATTACHARJEE (The Bioscan, 2015)
A study was development of putative SCAR markers from monomorphic bands of RAPD and ISSR primers. The races selected for studies were Type Race-1 (Hyderabad and Akola), Type Race-2, (Kanpur), Type Race-3, (Gurdaspur), Type Race-4 (New Delhi and Jabalpur). Primers used for developing SCAR marker for Fusarium oxysporum f.sp. ciceri were ISSR (GA) 8 YT ,(ATG) 6 ,(GA) 8 T) and RAPD OPA13 OPA18 and OPB14. These primers showed the monomorphic bands, these can be used for development of the putative of SCAR (Sequence Characterized Amplified Regions) markers for identification of Fusarium oxysporum f.sp.ciceri. The amplicon size 600 bp(ATG) 6 ,700 bp (GA) 8 YT and 650 bp of ISSR and 750 bp(OPA18),1.4 kb (OPB14),1500 and 800 bp of OPA 13 were eluted, isolated, confirmed and sequenced. The primers were designed with the sequenced information of these two fragments using primer.3.software and putative SCAR markers were developed. These set of markers were validated against the isolates of the pathogen collected from different locations of India representing various races of the pathogen. Races 1and 4 showed close virulence patterns on chickpea differentials.